Low‐Cost Carbon Xerogels Derived from Phenol–Formaldehyde Resin for Organic Electric Double‐Layer Capacitors. Issue 4 (17th February 2021) - Yoo, Jihoon; Yang, Inchan; Kwon, Dahye; Jung, Meenkyoung; Kim, Myung-Soo; Jung, Ji Chul
Abstract : In this study, low‐cost carbon xerogels (CXs) are successfully prepared by condensation of phenol and formaldehyde and applied to electrode materials for organic electric double‐layer capacitors (EDLCs). Condensation of resorcinol and formaldehyde is the most commonly used method for the synthesis of CXs because although resorcinol is more expensive than phenol, it has better reactivity with formaldehyde. For this reason, research on the synthesis of CXs derived from phenol–formaldehyde resin is potentially useful for decreasing CX cost. Thus, CXs are synthesized using phenol and formaldehyde while gradually increasing the amount of the catalyst to increase the reactivity between the two compounds. Through Fourier transform infrared spectroscopy and nitrogen adsorption–desorption isotherm analysis, successful synthesis of phenol–formaldehyde CXs is confirmed and it is found that a CX prepared with a phenol‐to‐catalyst molar ratio of 50 (PC_50) exhibits the largest surface area among the prepared CXs. Moreover, PC_50 shows good electrochemical performance as an electrode material for organic EDLCs due to its large surface area. In summary, a low‐cost CX with a large surface area and good electrochemical performance is successfully synthesized as an electrode for EDLCs using a phenol precursor, which offers greater cost efficiency compared to resorcinol. Abstract : Low‐cost carbon xerogels are prepared using phenol as a precursor for electric double‐layer capacitors (EDLC) and controlling the molar ratio of phenol to catalyst (P/C). Herein, a carbon xerogel synthesized under a condition of P/C = 50, exhibits good capacitance due to its large surface area. Consequently, phenol can be a good candidate for low‐cost carbon xerogels for high‐performance EDLCs.